Development and validation of a CpG island methylator phenotype‐related prognostic signature for cholangiocarcinoma. Issue 4 (29th September 2020) - Liang, Junnan; Liu, Tongtong; Liao, Jingyu; Zhang, Lu; Zhou, Mi; Xu, Weiqi; He, Yi; Cai, Guangzhen; Jin, Guannan; Song, Jia; Li, Ganxun; Liang, Huifang; et al.
Abstract: Cholangiocarcinoma (CCA) still has a very unfavorable prognosis with a very high mortality, which is complicated by a lack of prognostic biomarkers. In this study, CCA patients in the Gene Expression Omnibus (GEO) cohort were categorized into two subtypes. Differentially expressed and methylated genes were identified, and the impact of DNA methylation in the trans‐regulation of gene expression was investigated. Finally, a CIMP‐related methylation signature specific for CCA (CMSC) was trained in GEO and validated in the Tongji cohort. A subset of patients with CIMP‐H was identified, which was correlated with an unfavorable prognosis. Gene enrichment analysis implied the potential mechanism of CIMP as a promoter of carcinogenesis by regulating proliferation. The trans‐regulation among differentially methylated CpG sites and genes with the same change trends was positively correlated, while the converse situation showed a negative correlation. Notably, CMSC based on four genes could significantly classify CCA patients into low‐ and high‐risk groups in the GEO cohort, and the robustness of CMSC was validated in the Tongji cohort. The results of receiver operating characteristic analysis further indicated that CMSC was capable of highly sensitive and specific prediction of the patient outcomes in CCA. In conclusion, our work highlights the clinical significance of CMSC in the prognosis of CCA. Abstract : In this study, the CIMP‐related prognostic model, based on four genes was identified and validated for the first time, which acts as an independent prognostic factor to estimate prognosis in CCA and reflects the overall epigenetic alterations among the whole genome. In this study, the CIMP‐related prognostic model, based on four genes was identified and validated for the first time, which acts as an independent prognostic factor to estimate prognosis in CCA and reflects the overall epigenetic alterations in the whole genome.